WEBSITE INVENTORY MANAGEMENT SPARE PART INDUSTRY USING SCRUM METHOD - Clara, Monica; Andry, Johanes Fernandes (Universitas Teknokrat Indonesia, 2024)
The application of goods inventory in a warehouse for a company is one of the information technologies that help human life in carrying out their daily activities. Applying information technology can support company performance to compete with competitors, making it easier for them to manage and store data. Observation, interview, and literature studies is the several data collection methods used in research. In carrying out its business processes, there are problems experienced by companies, namely they have difficulty managing stock of goods, goods that arrive at the company are directly stored in warehouses that are not arranged in an orderly manner resulting in difficulties in searching, incoming and outgoing goods are not properly recorded, they do not know how many goods are in stock left or have run out due to the many types of spare part goods. This is what causes the goods ordered by customers to be delayed in the delivery process. In addition, repairs to heavy equipment, generators and ships requiring replacement of spare parts by company partners (customers) are delayed. The operational part of the company works not only in the office, but sometimes at home or even in a container depot. The solution to the problems that occur is that companies need a website-based inventory management application. This application was development using the Scrum method. This method is carried out for 4 months as many as 8 sprints. Then, the programming languages used in development applications are PHP code, HTML, CSS, JavaScript, Bootstrap Framework, and MySQL database management system. Application testing uses the black box method in accordance with the test scenario. The application's main menu consists of a dashboard, stock goods, incoming goods, outgoing goods, goods data, types, units, supplier, customer, and user settings, and reports. Applications are made for companies as a solution to solve problems.